Students Difficulties to Write Paraphrasing Text and Summarizing Text - Wildan Abdul Azis; Yanti Suryanti; Entis Sutisna (FKIP UNIVERSITAS PAKUAN, 2019)
This research entitled “students’ difficulties to write paraphrasing text and summarizing text”. Paraphrasing and summarizing are important for the students because the texts ask the students to rewrite the text by using their own words. In addition, paraphrasing and summarizing have similarities in the step of writing, but the texts are different. In conducting the research, descriptive method is used to conduct the research. The research is conducted to the fifth semester of English Education Study Program students who have been taking resume writing subject. For gaining the data, the writer uses documentation, questionnaire, and interview. After gaining the data, the result shows that the students face difficulties to write paraphrasing text and summarizing text, their difficulties come from various factors such as lack of vocabulary and lack of knowledge. In addition, the students face difficulties in paraphrasing and summarizing the text because they do not understand the basic knowledget of paraphrasing and summarizing, although paraphrasing and summarizing have techniques, but the students do not know how to write paraphrasing and summarizing well.